Psychology : A Very Short Introduction - Butler, Gillian and McManus, Freda (Karachi, Pakistan Oxford University Press, 2005)
Psychology is part of everyone's experience, it influences the way we think about everything. This book provides an understanding of some of psychology's leading ideas, and their practical relevance, making it useful for those interested in understanding the human mind.
Include Index and References.
Keywords: Psychology